2012
DOI: 10.1007/s11292-012-9165-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of the effectiveness of multisystemic therapy in the Netherlands: post-treatment changes and moderator effects

Abstract: Objective In the present randomized controlled trial, the effectiveness of multisystemic therapy (MST) in The Netherlands was examined. Moderator tests were conducted for ethnicity, age and gender. Methods The sample consisted of N0256 adolescents, referred because of conduct problems, and randomized to MST or treatment as usual (TAU). Assessments (questionnaires and observational ratings) took place before and immediately after the treatment. Results MST was more effective than TAU in decreasing externalizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 55 publications
5
50
0
Order By: Relevance
“…There have been documented reductions in criminal offending by both sexes. Sex-specific treatment effects were not found nor reported across any of these studies, and girls did no better or worse than boys did on outcomes in any single study, with the exception of Asscher et al (2013) who reported larger effects for boys than girls on hostility outcomes following MST. Does this prove that these three EBPs are generally equally effective for males and for females?…”
Section: Evidence-based Interventions For Youths Involved In the Juvementioning
confidence: 80%
See 2 more Smart Citations
“…There have been documented reductions in criminal offending by both sexes. Sex-specific treatment effects were not found nor reported across any of these studies, and girls did no better or worse than boys did on outcomes in any single study, with the exception of Asscher et al (2013) who reported larger effects for boys than girls on hostility outcomes following MST. Does this prove that these three EBPs are generally equally effective for males and for females?…”
Section: Evidence-based Interventions For Youths Involved In the Juvementioning
confidence: 80%
“…The results of these trials indicate that the interventions are associated with improved outcomes across a host of domains, and in particular, that they lead to reductions in delinquency and recidivism. In each study, the intervention was effective for the sample as a whole, and with a single exception (Asscher et al, 2013), no differences were identified with respect to outcomes based on sex. However, girls were underrepresented in these trials relative to the population base rates for JJ-involved youths, except for TFCO, in which the trials included only girls.…”
Section: Evidence-based Interventions For Youths Involved In the Juvementioning
confidence: 95%
See 1 more Smart Citation
“…7, 8, 9, 10 Therefore, caregiver monitoring, supervision, family cohesion and support, and provision of consistent rules and consequences are frequent targets of MST. When addressing these factors, MST therapists must be prepared to overcome barriers such as parental mental health problems, substance abuse, and poor parenting skills, all of which may be included in the ongoing conceptualization of problem behaviors.…”
Section: Mst Clinical Proceduresmentioning
confidence: 99%
“…The treatment effects of MST have also been linked to improved behavioral health symptoms 18 months after treatment among youth with antisocial and behavioral problems compared to youth who received wraparound services (Stambaugh et al 2007) or treatment-as-usual (Glisson et al 2010). The positive effects of MST in addressing problem behaviors among high-risk populations of offending youth have led to program adaptations for other at-risk populations of youth and families, including those with substance abuse problems (Henggeler et al 1999, 2006), serious conduct problems (Asscher et al 2013; Weiss et al 2013), serious emotional disturbance (Stambaugh et al 2007; Rowland et al 2005), and youth and families involved in the child protective services (MST-Child Abuse and Neglect or MST-CAN; Swenson et al 2010). The benefits of MST to reduce problem behaviors among high-risk youth and families have been corroborated by two meta-analytic studies, which suggest small to moderate treatment effect sizes on internalizing and externalizing symptoms among youth who participated in MST (van der Stouwe et al 2014; Curtis et al 2004; for a rebuttal, see; Littell et al 2005).…”
Section: Introductionmentioning
confidence: 99%